The Influence of Parental Involvement on Parent Satisfaction: The Moderating Effect of Parental Educational Level and the Number of Children - Shao, Mingming; He, Wei; Zhao, Li; Su, Yu-Sheng (Frontiers in Psychology, 2022)
With the changing of the place of school education from the classroom to home during the COVID-19 outbreak, there should be more educational caregiving from children’s parents when children learn online. Parental involvement including studying tutoring and psychological counseling in children’s online learning is the specific content of the educational caregiving, which is different from traditional face-to-face learning. More attention should be paid to parental involvement and their satisfaction with online learning effect. This study conducted a survey on the middle school students’ parents to establish a moderating model, exploring the influence of parental education level, the number of children, and parental involvement on online learning satisfaction. The results show that there is a significant positive correlation between parental involvement and satisfaction; Parental education level and the number of children play a moderating role in the relationship between parental involvement and parent satisfaction. The education level of parents has a negative moderating effect, while the number of children has a positive moderating effect. An interesting finding is that the number of children has a very low influence on parental participation.